Soluble RAGE Treatment Delays Progression of Amyotrophic Lateral Sclerosis in SOD1 Mice - Juranek, Judyta K.; Daffu, Gurdip K.; Geddis, Matthew S.; Li, Huilin; Rosario, Rosa; Kaplan, Benjamin J.; Kelly, Lauren; Schmidt, Ann Marie (Frontiers in Cellular Neuroscience, 2016)
The etiology of amyotrophic lateral sclerosis (ALS), a fatal motor neuron disorder characterized by progressive muscle weakness and spasticity, remains largely unknown. Approximately 5-10% of cases are familial, and of those, 15-20% are associated with mutations in the gene encoding Cu/Zn superoxide dismutase (SOD1). Mutations of the SOD1 gene interrupt cellular homeostasis and contribute to cellular toxicity evoked by the presence of altered SOD1, along with other toxic species, such as advanced glycation end products (AGEs). AGEs trigger activation of their chief cell surface receptor, RAGE (receptor for advanced glycation end products), and induce RAGE-dependent cellular stress and inflammation in neurons, thereby affecting their function and leading to apoptosis. Here, we show for the first time that the expression of RAGE is higher in the SOD1 transgenic mouse model of ALS versus wild-type mouse spinal cord. We tested whether pharmacological blockade of RAGE may delay the onset and progression of disease in this mouse model. Our findings reveal that treatment of SOD1 transgenic mice with soluble RAGE (sRAGE), a natural competitor of RAGE that sequesters RAGE ligands and blocks their interaction with cell surface RAGE, significantly delays the progression of ALS and prolongs life span compared to vehicle treatment. We demonstrate that in sRAGE-treated SOD1 transgenic animals at the final stage of the disease, a significantly higher number of neurons and lower number of astrocytes is detectable in the spinal cord. We conclude that RAGE antagonism may provide a novel therapeutic strategy for ALS intervention.